Awareness and Perception of Muslim Community Towards Islamic Banking in Yogyakarta - Agustin, Annisa Rahmadania; Wiranatakusuma, Dimas Bagus; Sobari, Indriyani (Proceedings of Universitas Muhammadiyah Yogyakarta Graduate Conference, 2023)
This study was undertaken to explain how the lack of public knowledge of Islamic banking in Indonesia affects the degree of awareness of the Muslim community about Islamic banking. This study's objective is to uncover and evaluate the degree of knowledge and attitudes of the Muslim community about Islamic banking in Yogyakarta, as well as the variables that influence this awareness. This research was conducted using a quantitative method and distributing questionnaires to 30 Muslim communities who live and work in the Yogyakarta area. Using the Likert Scale, participants were also required to indicate their level of agreement with statements on their views and knowledge of Islamic banking's essential principles and features. According to the data, some Yogyakartans are already familiar with the existence of Islamic banks. In contrast, they are unfamiliar with Islamic banking products and services, as well as financing techniques such as Musharakah, Mudharabah, Murabahah, and Ijaraah. Economics, environment, psychology, and religion also have a significant influence in shaping the Muslim community's understanding and attitudes of Islamic banking in Yogyakarta. By looking at the findings, it is advised that Islamic banks should criticize the deficiencies of implementing Islamic values in Islamic banks.